2016
DOI: 10.1016/j.neuroimage.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D orientation distribution functions measured with confocal microscopy and diffusion MRI

Abstract: The ability of diffusion MRI (dMRI) fiber tractography to non-invasively map three-dimensional (3D) anatomical networks in the human brain has made it a valuable tool in both clinical and research settings. However, there are many assumptions inherent to any tractography algorithm that can limit the accuracy of the reconstructed fiber tracts. Among them is the assumption that the diffusion-weighted images accurately reflect the underlying fiber orientation distribution (FOD) in the MRI voxel. Consequently, val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 70 publications
(99 reference statements)
5
110
0
Order By: Relevance
“…Future validation of our preliminary findings could include: analysis of tissue from areas beyond the spinal cord; extension of the histology to the third dimension50, 51; further confirmation from in vivo data; characterization of more complex morphological features of glial cells52; more accurate diffusion MRI signal modeling43, 53; analysis of other quantitative MRI metrics (such as those from relaxometry, magnetization transfer techniques or susceptibility imaging).…”
Section: Discussionmentioning
confidence: 86%
“…Future validation of our preliminary findings could include: analysis of tissue from areas beyond the spinal cord; extension of the histology to the third dimension50, 51; further confirmation from in vivo data; characterization of more complex morphological features of glial cells52; more accurate diffusion MRI signal modeling43, 53; analysis of other quantitative MRI metrics (such as those from relaxometry, magnetization transfer techniques or susceptibility imaging).…”
Section: Discussionmentioning
confidence: 86%
“…For example, we anticipate future releases to be augmented with high resolution histological data (Sun et al 2015). This could, for example, be used for validating the accuracy of various diffusion MRI techniques for reconstructing an estimate of local fiber orientation distributions (Choe et al 2012; Schilling et al 2016), or confirming the validity of fiber tractography (Gao et al 2013; Dyrby et al 2007). Incorporation of fMRI, PET, and brain connectivity information is also readily performed.…”
Section: Discussionmentioning
confidence: 99%
“…Together, this allows acquisition of data with higher signal-to-noise ratios and at a higher resolution compared to in vivo studies. We chose to include ex vivo templates because of their significantly increased contrast, and the additional value of the use of ex vivo and subsequent histology as a means to validate MRI techniques and aid image interpretation (Azadbakht et al 2015; Bastiani et al 2016; Calabrese et al 2015; Choe et al 2012; Knosche et al 2015; Leergaard et al 2010; McNab et al 2009; Schilling et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Human studies are scarce due to the invasive nature of resection and biopsies but initial studies have shown a relation between diffusion anisotropy and tissue microstructure in brain (Ronen et al, 2014), tumor (Szczepankiewicz et al, 2015) and prostate tissue (Bourne et al, 2012). In animals, the investigated features range across structure eccentricity and orientation (Budde and Frank, 2012; Khan et al, 2015; Schilling et al, 2016), neurodegeneration (Jelescu et al, 2016; Jespersen et al, 2010; Kamagata et al, 2016), and axonal diameter (Barazany et al, 2009). However, the link between microscopic tissue heterogeneity and diffusional variance has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%